Comparison of technical and physiological characteristics of prepubescent soccer players of different ages - Fernandez-Gonzalo, R.; de Souza-Teixeira, F.; Bresciani, G.; Garcia-Lopez, D.; Hernandez-Murua, J. A.; Jimenez-Jimenez, R.; de Paz, J. A. (The Journal of Strength and Conditioning Research, 2010)
Although soccer is one of the most widely played sports around the world, studies about young players and the success factors in soccer are still scarce. Therefore, the purpose of this study was to offer some insight into the factors contributing to success in this sport and to describe how physiological and technical performance evolves in young soccer players. Soccer technical skills during match play, maximum voluntary isometric contraction and power of lower limbs, jumping ability and endurance parameters were assessed in 30 prepubescent male soccer players with the same experience in soccer training. Subjects were divided into 2 groups of 15 children, a younger group (YG), aged 9.4 ± 0.3 years, and an older group (OG), aged 11.8± 0.2 years. Correlations between technical and physiological parameters were also described. Significant difference was set at p < 0.05. Differences between YG and OG appeared in physiological performance, mainly in VO2peak expressed in absolute values, VO2 at different speeds, perceived exertion in treadmill test, jump performance, strength, and peak power of lower limbs. Among the technical skills measured, significant differences were found only in heading. The differences found between groups showed that most physical capacities that were measured here have an important increase during the first stages of puberty, pointing out that a specific training at these ages is necessary to get an appropriate basis for future performance. Besides, over 30% of the technical performance measured in this study can be explained with the physiological parameters. The data shown in this paper help to determine the most important capacities in youth soccer, which can facilitate the development of more appropriate selection models and trainings.